La lúdica como dimensión de la Educación Corporal. El juego del deseo y el placer (2011)
ABSTRACT: This article is a bid to move new roads, re-run of the concepts and ideas that are fun and we have indicated the path that so far we have apprehended, we have internalized as an option attitudinal human development as an opening through the enjoyment and pleasure. Modernity has shown its influence through its dualism, this being incisive in understanding and subjective concept formation with us today in this present and the fun has not escaped it, unlike blends into a speech multifaceted and rich in adjectives that denote integral and unique beings, but in the background, we can uncover through its stir, objectivity, a playful discourse operation turns out to be permeated modern discourse where cause and effect relationship becomes relevant to the extent that they continue to meet needs, absence, leading to the fun that is not seen as a process, but as states of being, allowing a glimpse of a fragmentation of it. Concepts such as the desire then from Deleuze, allow us to demonstrate in other ways, other perspectives, other ideas and other ways that the fun has not considered and this fact motivates us to “shake” a bit in that line, where fun has only embraced the positive and well - being of the human being as dominant factor in his theory.